Pyrophosphate ion-responsive alginate hydrogel as an effective fluorescent sensing platform for alkaline phosphatase detection. Issue 76 (6th September 2019) - Li, Yong; Huang, Zhen-Zhong; Weng, Yuhao; Tan, Hongliang
Abstract : A Cu 2+ -crosslinked alginate hydrogel can encapsulate fluorescent carbon dots for visually monitoring PPi-stimulated gel–sol transition and the further detection of ALP. Abstract : A pyrophosphate ion (PPi)-responsive alginate hydrogel was fabricated by using Cu 2+ as a crosslinker. Benefiting from the ultrahigh affinity of Cu 2+ to PPi, which can discriminate PPi from phosphate ions and other anions, the incorporation of carbon dots enables the alginate hydrogel to be an effective fluorescent sensing platform for the detection of alkaline phosphatase.